Characteristics of the Intestinal Flora of TPOAb-Positive Women With Subclinical Hypothyroidism in the Second Trimester of Pregnancy: A Single-Center Prospective Cohort Study - Wu, Min; Yang, Yuxi; Fan, Yali; Guo, Shan; Li, Tianhe; Gu, Muqing; Zhang, Tingting; Gao, Huimin; Liu, Ruixia; Yin, Chenghong (Frontiers in Cellular and Infection Microbiology, 2022)
Pregnant women are at high risk of developing subclinical hypothyroidism (SCH), and anti-thyroid peroxidase antibody (TPOAb) positivity can further inhibit thyroxine synthesis. Emerging evidence indicates that intestinal flora can modulate metabolic and immune homeostasis. The characteristics of intestinal flora of TPOAb-positive women with SCH in their second trimester of pregnancy have not been reported. This single-center prospective observational cohort study investigated gut microbial composition and metabolic function using sequencing of the 16S rRNA gene in fecal samples from 75 TPOAb-positive women with SCH and 90 TPOAb-negative women with SCH during their second trimester of pregnancy. Women were treated with no levothyroxine (LT4), low-dose LT4 (≤50ug/d), or high-dose LT4 (>50ug/d). Taxonomic analysis showed Firmicutes and Bacteroidetes were the dominant phyla, followed by Actinobacteria and Proteobacteria. Faecalibacterium, Bacteroides, Prevotella 9, Bifidobacterium, Subdoligranulum, Lachnospira, and Megamonas were the predominant genera. The intestinal flora of TPOAb-positive women with SCH who received no LT4 was characterized by bacterial amplicon sequence variants (ASVs)/operational taxonomicunits (OTUs) enriched in the genus Subdoligranulum. The intestinal flora of TPOAb-positive women with SCH who received low-dose or high-dose LT4 were characterized by bacterial ASVs/OTUs depleted of the species Ruminococcus sp._or Bacteroides massiliensis, respectively. A total of 19 metabolic functions of intestinal flora, mainly involving in lipid and amino acid metabolism, discriminated TPOAb-positive and TPOAb-negative women with SCH. Our study suggests that there are differences in the composition and metabolic function of intestinal flora from TPOAb-positive and TPOAb-negative women with SCH treated with different doses of LT4 in the second trimester of pregnancy. The findings provide insight into intestinal flora as novel targets for the treatment of TPOAb-positive women with SCH during pregnancy.